1999
DOI: 10.1097/00005537-199907000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Clinically Negative Neck in Oral Squamous Cell Carcinoma

Abstract: T1 tumors do well with neck treatment other than careful observation. The data suggest that patients with T2 and T3 oral squamous cell carcinoma should undergo surgical resection of their primary tumor site and elective neck dissection. Patients with T4 oral cavity lesions should routinely undergo neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 29 publications
1
30
0
3
Order By: Relevance
“…Several reports have described the results of elective neck dissection versus observation or watching for patients with N0 early tongue cancers, and it has been reported that the survival rate of "watched" patients was worse than that of patients having elective neck dissection (Cunningham et al 1986;Ho et al 1992;Lydiatt et al 1993;Yuen et al 1997;Persky and Lagmay 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the results of elective neck dissection versus observation or watching for patients with N0 early tongue cancers, and it has been reported that the survival rate of "watched" patients was worse than that of patients having elective neck dissection (Cunningham et al 1986;Ho et al 1992;Lydiatt et al 1993;Yuen et al 1997;Persky and Lagmay 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Los autores que recomiendan tratamiento electivo de las cadenas ganglionares y especialmente aquellos basados en series quirúrgicas, sustentan su opinión en base al alto índice de metástasis ganglionares ocultas, que oscilan entre 20-40% [1][2][3][8][9][10] . Las dos principales críticas al tratamiento quirúrgico electivo podrían ser, por un lado, que no es un tratamiento exento de complicaciones, con tasas de mortalidad de hasta el 2-5% según series, y por otro lado la cirugía electiva no previene el 100% de las recidivas ganglionares ulteriores; de forma adicional, casi ningún estudio ha demostrado retrospectivamente mejora en control ganglionar y supervivencia al comparar la cirugía electiva con la observación cervical estrecha.…”
Section: Discussionunclassified
“…Sin embargo, dado que el estudio era retrospectivo y ambos grupos no estaban bien balanceados, no pudieron concluir el beneficio de uno u otro tratamiento. En esta misma línea, de forma global y sin tener en cuenta los estadios clínicos, aunque en la mayoría de las series quirúrgicas las tasas de recidiva ganglionar varían entre el 0-20% en los pacientes sometidos a cirugía electiva frente a 20-35% en los pacientes observados, ningún estudio ha demostrado diferencias significativas entre ambas modalidades de tratamiento, quizá por el bajo número de pacientes en todos los estudios 1,10,12,13 . Por otro lado, el tratamiento electivo de las cadenas ganglionares con radioterapia, ha demostrado beneficio frente a la observación cervical en algunas series y en aquellas en las que las diferencias no alcanzaron significación estadística, la tendencia era hacia una menor proporción de recidivas ganglionares en los pacientes tratados con irradiación electiva.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Elective neck dissection as a treatment for patients with early-stage oral tongue cancers and clinically normal necks remains a controversial issue (Haddadin et al, 1999;Hughes et al, 1993;Keski-Santti et al, 2006;O'Brien et al, 1986;Veness et al, 2005;Yuen et al, 1997). Several reports have described the results of immediate elective neck dissection versus delayed elective neck dissection, that is, performing the surgery after the patient is observed or watched to have developed of earlystage N0 tongue cancers, and it has been reported that the survival rate of "watched" patients was worse than that of patients having elective neck dissection (Cunningham et al, 1986;Ho et al, 1992;Lydiatt et al, 1993;Persky and Lagmay, 1999;Yuen et al 1997).…”
Section: Introductionmentioning
confidence: 99%